EVALUATION OF THE QUALITY OF WORK LIFE OF STUDENTS OF A PUBLIC HIGH SCHOOL IN SOUTHERN SONORA (Lex localis - Journal of Local Self-Government, 2025)
The objective of this study was to evaluate the quality of work life of high school students in southern Sonora, using a structured instrument to identify the factors that affect their well-being and academic performance. We worked with a representative sample of 326 students, selected through probabilistic sampling in which the results indicated that 78.8% perceive their quality of life favorably in secondary school, considering that they have the adequate resources for their academic training. For data collection, a questionnaire based on previous studies was applied, composed of 32 items on the Likert scale and divided into three main dimensions: quality of student life, secondary identity and academic performance.The research took a quantitative and experimental approach. In the initial phase, the importance of the topic and its scarce exploration in the local context were justified. A literature review was conducted to define the key variables and a representative sample of public high school students from southern Sonora was selected. The questionnaire was administered under a standardized process, guaranteeing the confidentiality of the responses. Subsequently, statistical methods were used to analyze the data and determine patterns between the dimensions studied.According to the results, 40.2% of the students agreed and 33.7% totally agreed that their academic load allows them to balance their personal lives. However, 12.9% expressed disagreement regarding the freedom to express their opinions at school. In general terms, 81.6% expressed satisfaction with their student experience. The reliability analysis of the instrument reflected a Cronbach's alpha coefficient of 0.893, indicating high internal consistency. In addition, 75.2% of students said they understood their academic responsibilities, while 78.8% identified with high school goals. Regarding conflict resolution in the institution, 38.3% considered the existing mechanisms adequate. Regarding the treatment of teachers, 49.1% of the students expressed feeling totally satisfied.